Neurodegenerative Disease and the Experience of Homelessness - Piña-Escudero, Stefanie Danielle; López, Lucía; Sriram, Sandeepa; Longoria Ibarrola, Erika Mariana; Miller, Bruce; Lanata, Serggio (Frontiers in Neurology, 2021)
Neurodegenerative diseases of the brain (NDDB), may play a role eliciting homelessness in a significant proportion of vulnerable older adults. This article aims to explore relationships between homelessness and NDDB in a cohort of research participants enrolled in an academic center. Methods: We reviewed charts of the Memory and Aging Center (MAC) of the University of California, San Francisco´s database and included research participants with NDDB that had direct relationship to homelessness. NDDB was diagnosed via neurological, functional, neuropsychological and biomarker assessments. Non-parametric tests were used for analysis. Thirteen participants were found to have a direct relationship with homelessness. Participants were divided into two groups: Those who experienced homelessness while symptomatic from a NDDB but before formal diagnosis (n=5, Group 1); and participants with formally diagnosed NDDB who exhibited a new propensity towards homelessness (n=8, Group 2). Compared to Group 2, participants in Group 1 were younger (p=0.021) and showed similar results in the neuropsychological evaluation. In both groups, the most prevalent diagnosis was frontotemporal dementia. In Group 1, the majority of participants became homeless in the setting of a fragile socioeconomic situation and informants believed that NDDB contributed or caused their homeless state. In Group 2, a new propensity towards homelessness became manifest in different ways and it stood out that all of these participants were well supported by family and friends during their illness. Conclusions and Relevance: NDDB may be precipitating homelessness among vulnerable older adults, particularly in the setting of challenging socioeconomic circumstances and unsupportive living environments.